Relationship principal-agent or principal-principal conflicts and islamic banks performances / Azilawati Banchit, Zakaria Boulanouar, Nirosha Hewa Wellalage and Sazali Zainal Abidin - Boulanouar, Zakaria; Wellalage, Nirosha Hewa; Zainal Abidin, Sazali; Banchit, Azilawati (Faculty of Business Management, 2013)
Recently, it has been identified that firms in developing economies suffer an agency conflict called principal-principal (PP) conflict, distinct from the traditional principal-agent (PA) conflicts. Little is known about these conflicts in the Islamic banks. Using five years panel from 37 Islamic banks across ten countries, this paper investigates the relationship of these conflicts and their impact to the banks‟ performances. Results show that PA is the main concern, with inconclusive results for PP conflicts. This cross-country study helps to establish the existence of agency conflicts in Islamic banking and adds to the growing knowledge of PP conflicts.